Review Essays - Various Authors (Studies in 20th & 21st Century Literature, 1991)
Awareness and Amnesia: Freud, Proust and Lacan: Theory as Fiction, by Malcolm Bowie. Mary Lydon The Modernist Novel in Spain. Transparent Simulacra: Spanish Fiction 1902-1906, by Robert Spires. Roberta Johnson Staging the End of Individualism: Sloterdijk's Postmetaphysical Dramaturgy. Thinker on Stage: Nietzsche's Materialism, by Peter Sloterdijk. Alan D. Schrift
Keywords: Awareness and Amnesia: Freud Proust and Lacan: Theory as Fiction; Malcolm Bowie; The Modernist Novel in Spain; Transparent Simulacra: Spanish Fiction 1902-1906; Robert Spires; Staging the End of Individualism: Sloterdijk& #x27; s Postmetaphysical Dramaturgy; Thinker on Stage: Nietzsche& #x27; s Materialism; Peter Sloterdijk; Mary Lydon; Roberta Johnson; Alan D. Schrift